Estimation of economic values for traits of dairy sheep: II. Model application to a production system with one lambing per year - Wolfová, M; Wolf, J; Krupová, Z; Margetín, M (Journal of dairy science, 2009)
A bioeconomic model for dairy sheep was applied to a production system with one lambing per year. The classical extensive Carpathian system with indoor winter lambing, traditional weaning, sale of surplus lambs before Easter, and a summer milking period with ewes on pasture was modeled. The economic values of 15 performance and functional traits were calculated for the Slovakian Improved Walachian multi-purpose breed. The economic values per unit increase in the traits were 0.32 euro/kg of milk yield during the standardized milking period of 150 d, 0.29 euro/0.1% milk fat, 0.42 euro/0.1% milk protein, 0.28 euro/% and 0.56 euro/% for conception rates of female lambs and ewes, respectively, 0.20 euro/0.01 lamb born, 0.0036 euro/% and 0.0040 euro/% for lamb survival at birth and until weaning, respectively, 0.65 euro/kg of birth weight, 0.032 euro/g per d daily gain from birth until weaning, -0.030 euro/kg of mature weight, -0.38 euro/0.1 and -0.21 euro/0.1 conformation quality grade for weaned lambs and adult sheep, respectively, 0.42 euro/kg of fleece weight and 11.10 euro/year of productive lifetime for ewes.
Keywords: krmivo pro zvířata; těhotenství; Software; Weaning; zvířata; odstavení; Models, Biological; reprodukovatelnost výsledků; Sheep; Animal Feed; Time Factors; Parturition; software; biologické modely; Dairying; mlékárenství; ovce; časové faktory; náklady a analýza nákladů; ženské pohlaví; Animals; Costs and Cost Analysis; Reproducibility of Results; porod; Pregnancy; Female